Perceptions of Criminal and Gang Involvement Among College Student-Athletes - Alpert, Geoff (2013)
The involvement of youth and young adults in gangs and other criminal activities continues to be a serious threat and grounds for concern among a variety of stakeholders on college campuses and beyond. The extant literature examining the criminality of intercollegiate student-athletes is limited to media accounts or research focused on few types of offenses or athletics programs. The presence and impact of gangs in institutions such as secondary education and the military has been documented, but the expansion of gangs to college athletics has not been empirically verified despite media portrayals. The current study addresses these gaps in knowledge of criminally and gang-involved college student-athletes with information provided by athletics directors and campus police chiefs. Findings from both groups of key informants show that individuals involved with gangs and other criminal offenses participate in college athletics. However, few athletics directors and campus police chiefs reported the presence of gang-involved athletes on their own campuses